2009
DOI: 10.1093/eurheartj/ehp273
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein improves risk prediction in patients with acute coronary syndromes

Abstract: Elevated C-reactive protein level is a modest but independent predictive factor of 30-day mortality in ACS patients, even after adjustment for co-morbidities, haemodynamic conditions, and treatment. Combined with the GRACE risk score, C-reactive protein information improves risk classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 24 publications
1
70
2
1
Order By: Relevance
“…All biomarkers investigated in the present study, except for FGF23, have been linked to adverse outcomes in NSTE-ACS (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)23 ). FGF23 is emerging as a prognostic biomarker in chronic kidney disease (35 ) and stable coronary artery disease (36 ), which prompted us to explore it for the first time in NSTE-ACS.…”
Section: Discussionmentioning
confidence: 86%
“…All biomarkers investigated in the present study, except for FGF23, have been linked to adverse outcomes in NSTE-ACS (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)23 ). FGF23 is emerging as a prognostic biomarker in chronic kidney disease (35 ) and stable coronary artery disease (36 ), which prompted us to explore it for the first time in NSTE-ACS.…”
Section: Discussionmentioning
confidence: 86%
“…29,30 CRP can also be produced locally in atherosclerotic lesions. 31 Although CRP is generally considered to be an inflammatory marker or an atherosclerotic marker, [32][33][34] CRP also plays a role as a mediator of atherosclerosis. CRP directly influences several phases of atherosclerosis via complement activation, apoptosis, vascular cell activation, monocyte recruitment, lipid accumulation, and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased hs-CRP values correlate with other risk scores in ACS. In one study, Schiele et al (22) demonstrated an independent predictive role of CRP in ACS patients; patients in the highest quartile of CRP showed increased mortality rates at 30 days of follow-up. Hence, in a setting of ACS, the hs-CRP value may be combined with well-validated risks such as TIMI and Global Registry of Acute Coronary Events scores, and helps in better predicting adverse events.…”
Section: Hs-crp (Mg/dl) Hs-trop T (Ng/ml) ---------------------------mentioning
confidence: 99%